Estruturação de uma metodologia para projeto de sistemas de aproveitamento de águas pluviais em edificações - Roggia, Melissa Neis (2007)
The lack of water is one of the world s worst problems that may affect the survival of human beings. Disordered use, waste, and demand growth are some of the reasons that contribute to increase the lack of potable water in the planet. XXI century is considered the urban age, being predicted that two third of the world population will be living in cities by the year 2025. Intensified concentration of population in cities and speed urbanization will reach more serious and critical lack of water situations, also accidents involving cities flooding. Brazil presents one of the greatest hydro beds in the world. Nevertheless, lack of potable water in several regions has been provoked by the unbalance between the demographic, industrial and agricultural distribution. Many measurements are going to be employed to fight the lack of water, as the conscious use by the population, control and inspection, so the fountainhead won t be polluted and the polluted beds will be recovered. Reutilization of water and employment of pluvial water, for non-potable intentions have grown. Exploitation of pluvial waters for non-potable use is a measure adopted in several countries for years. Rain is a source of water effortlessly available to anyone, so it is not correct to throw it completely into the draining network. However, it is necessary that a worry about implementation of pluvial waters systems occur, because many times the system may be executed without the proper care for water quality, and problems concerning the public health of population may appear. This way, the purpose of this work was structure a methodology for the system of pluvial waters employment in edifications; in a way to guarantee that the exploitation of these systems won t be inappropriately executed, what may compromise its credibility and the consumer s health. Subsequently, a study of several methods, achievement of technologies and utilization of pluvial waters was accomplished, which were validated by analysis and study of cases in three typologies of edification. Based on these studies was evident that the exploitation of pluvial waters must be considerate as a necessary item to be realized in all new edifications, as a way to reduce consume of potable water and cases of urban flooding. Still, was also obvious that is necessary and urgent the creation of a specific normalization and the standardization of non-potable water employment